PENGGUNAAN KRITERIA WATSON UNTUK MENGANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL MATERI GARIS DAN SUDUT - Dina Fitri Nurhidayah; Rippi Maya (IKIP Siliwangi, 2021)
The purpose of this study was to analyze student errors in solving a number of questions on line and angle material using Watson's criteria. The study method used is descriptive qualitative. Class VIII students at one of the MTs in Ciwidey are the research subjects in this study. Furthermore, 3 students were taken as samples with different error levels. The data analysis technique was carried out through 3 stages, namely examining student answers by referring to 8 errors according to Watson, presenting the results of the study in the form of tables and narratives, and conclusions based on research results. From the results of the study, a minor mistake made by students was not including the final conclusion (missing conclusions). Meanwhile, students with errors are making mistakes in the use of problem solving procedures, and do not include final conclusions. And students with high errors make mistakes by including inappropriate data, not using appropriate procedures, missing data and not including conclusions. The errors in indirect manipulation, response level conflicts, hierarchical ability problems and other than the seven errors were not found in the results of this study.